Diving deeper into jellyfish: The rich population of jellyfish galaxies in Abell 901/2. Issue Volume 15:Issue S359(2020) (March 2019) - Roman de Oliveira, Fernanda; Chies Santos, Ana; Ferrari, Fabrício; Lucatelli, Geferson
Abstract: Jellyfish galaxies are the most striking examples of galaxies undergoing ram pressure stripping – the removal of gas as a result of a hydrodynamic friction in dense environments. As part of the OMEGA (OSIRIS Mapping of Emission-line Galaxies in Abell 901/2) survey, we have identified the largest sample of jellyfish galaxies in a single system to this date, located in the Abell 901/2 multi-cluster system at z ˜ 0.165. We present our results with a detailed description of this sample regarding their very high star formation rates and their unique spatial distribution pattern that can be explained as a result of the merging system triggering ram pressure stripping events. Furthermore, we also show the results of our most recent morphometric studies where we use Morfometryka as a tool to characterise the morphologies and structural evolution of jellyfish galaxies. Our morphometric analysis shows that jellyfish galaxy candidates have peculiar concave regions in their surface brightness profiles. Therefore, these profiles are less concentrated (lower Sérsic indices) than other star forming galaxies that are not experiencing such extreme ram pressure effects.